Divergent total synthesis of the revised structures of marine anti-cancer meroterpenoids (+)-dysiherbols A–E. Issue 12 (6th March 2023) - Chong, Chuanke; Chang, Le; Grimm, Isabelle; Zhang, Qunlong; Kuang, Yang; Wang, Bingjian; Kang, Jingyi; Liu, Wenhui; Baars, Julian; Guo, Yuanqiang; Schmalz, Hans-Günther; Lu, Zhaoyong
Abstract : A concise and divergent enantioselective total synthesis of the revised structures of marine anti-cancer sesquiterpene hydroquinone meroterpenoids (+)-dysiherbols A–E was accomplished using dimethyl predysiherbol as a key common intermediate. Abstract : We report here a concise and divergent enantioselective total synthesis of the revised structures of marine anti-cancer sesquiterpene hydroquinone meroterpenoids (+)-dysiherbols A–E (6–10 ) using dimethyl predysiherbol 14 as a key common intermediate. Two different improved syntheses of dimethyl predysiherbol 14 were elaborated, one starting from Wieland–Miescher ketone derivative 21, which is regio- and diastereoselectively α-benzylated prior to establishing the 6/6/5/6-fused tetracyclic core structure through intramolecular Heck reaction. The second approach exploits an enantioselective 1, 4-addition and a Au-catalyzed double cyclization to build-up the core ring system. (+)-Dysiherbol A (6 ) was prepared from dimethyl predysiherbol 14 via direct cyclization, while (+)-dysiherbol E (10 ) was synthesized through allylic oxidation and subsequent cyclization of 14 . Epoxidation of 14 afforded allylic alcohol 45 or unexpectedly rearranged homoallylic alcohol 44 . By inverting the configuration of the hydroxy groups, exploiting a reversible 1, 2-methyl shift and selectively trapping one of the intermediate carbenium ions through oxy-cyclization, we succeeded to complete the total synthesis of (+)-dysiherbols B–D (7–9 ). The total synthesis of (+)-dysiherbols A–E (6–10 ) was accomplished in a divergent manner starting from dimethyl predysiherbol 14, which led to the revision of their originally proposed structures.